Immunohistochemical analysis of candidate gene product expression in the duodenal epithelium of children with coeliac sprue. Issue 9 (1st September 2001) - Barshack, I; Goldberg, I; Chowers, Y; Weiss, B; Horowitz, A; Kopolovic, J
Abstract : Background —Coeliac sprue is a chronic disease, in which there is a characteristic mucosal lesion of the small intestine and impaired nutrient absorption, which improves upon the withdrawal of wheat gliadins and related grain proteins from the diet. Biopsy specimens demonstrate diffuse enteritis with pronounced atrophy or total loss of villi. There is also a long term risk of malignant disease. Aims —To compare the immunoexpression of DCC (deleted in colon cancer), p53, E-cadherin, and β-catenin in the duodenal mucosa of children with coeliac disease with that seen in children with no evidence of small intestinal disease. Methods —To gain more insight into the genetic and immunohistochemical alterations of the duodenal epithelium in coeliac disease, 21 endoscopic biopsies from children with coeliac disease and 10 duodenal biopsies from children without coeliac disease were immunohistochemically evaluated for p53, DCC, E-cadherin, and β-catenin. Results —DCC expression was not reduced in patients with coeliac disease compared with those without coeliac disease. p53 positive nuclear immunostaining was seen in seven of the 21 patients with coeliac disease. Positive nuclear staining was seen mainly in the deep and the lateral aspects of the crypts. All patients in the control group were negative for p53. In nine and three of the 21 patients with coeliac disease, respectively, the immunohistochemical expression of E-cadherin and β-catenin was reduced. However, both E-cadherin and β-catenin immunostaining in the control group was not altered. Conclusions —E-cadherin and β-catenin were reduced in the duodenal epithelium of children with coeliac disease when compared with normal mucosa. p53 was overexpressed in the duodenal mucosa of patients with coeliac disease. The reduced expression of E-cadherin and β-catenin and p53 overexpression may contribute to the morphological changes seen in the small intestinal mucosa in coeliac disease.